A high-throughput microfluidic biochip to quantify bacterial adhesion to single host cells by real-time PCR assay - Zhang, Rui (2013)
A high-throughput microfluidic poly-(dimethylsiloxane) biochip was developed to quantify bacterial adhesion to single host cells by real-time PCR assay. The biochip is simply structured with a two-dimensional array of 900 micro-wells, one inlet, and one outlet micro-channels. Isolation of single infected host cells into the individual micro-wells of the biochip was achieved by one-step vacuum-driven microfluidics. The adhered bacterial cells were then quantified by direct on-chip real-time PCR assay with single-bacterium-detection sensitivity. The performance of this microfluidic platform was demonstrated through profiling of the association of a common bacterial pathogen, Pseudomonas aeruginosa, to single host human lung epithelial A549 cells, revealing an adherence distribution that has not been previously reported. This microfluidic platform offers a simple and effective tool for biologists to analyze pathogen–host interaction at the single-cell level without the necessities of fluorescence labeling. The chip can similarly be used for other PCR-based applications requiring single-cell analysis.